PENERAPAN BIAYA ADMINISTRASI PEMBIAYAAN DI KSPPS BAITUL TAMWIL MUHAMMADIYAH MULIA DALAM PERSPEKTIF HUKUM ISLAM - Muhammad rom rafsanjani romadhon; abdul wahab (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
Baitul Mal wat-Tamwil (BMT) is a cooperative-shaped institution. BMT in conducting financial management with the principle of the share of the outcome, buying and selling, and saving money (Wadi ‘ah). BMT in realizing financing, also apply the administrative cost of financing as a pre-requisite to be paid by the financing members. BMT as a financial institution that emerged from the implications of state recognition of Islamic laws in its operation must be strictly based on the Quran and Al-Hadist. In this research, there will be a survey on the implementation of financing administration costs in the Baitul Tamwil Muhammadiyah Mulia in Babat Lamongan in the perspective of Islamic law. The data in this study is the primary data obtained from the BMT and secondary data in the form of books that support the research. The data collection methods are observations, interviews and documentation. The results showed the Baitul Tamwil Muhammadiyah Mulia Babat Lamongan set the administrative fee based on a percentage of the nominal ceiling financing so that it will cause a different increase and expense for the nominal financing of different. This shows the Baitul Tamwil Mulia Muhammadiyah Babat Lamongan took advantage of financing administration management. This is not in accordance with the sharia based on Al-Quran and Al-Hadith which is interpreted in the Fatwa of the National Sharia Council of the Indonesian Ulema assembly No: 11/DSN-MUI/IV/2000 about the Kafalah and Fatwa of the National Sharia Board (DSN) of the Indonesian Ulama Council (MUI) NO. 44/DSN-MUI/VIII/2004 about multi-service Ijarah financing.Key Words :  KSPPS, Biaya Administrasi Pembiayaan, Hukum Islam